Comparative Analysis of Regional Readiness for the Implementation of Artificial Intelligence (AI) as a Support for Bank Financing Decision Making in Indonesia - Ismail Ismail; Rista Nuraeni; Esy Delia Lewaherilla; Parman Parman (AIBPM Publisher, 2026)
Development Artificial Intelligence (AI) is driving the transformation of the banking sector, but readiness for its implementation in Indonesia still faces regional disparities. This study aims to comparatively analyze regional readiness for the application of AI to support bank financing decision-making. The study uses cross-sectional data from 38 provinces in 2025, covering Third Party Funds (DPK), the Indonesian Digital Society Index (IMDI), Average Years of Schooling (RRLS), the Human Development Index (HDI), and Gross Regional Domestic Product (GRDP). The analysis was conducted using the Ordinary Method. Least Squares (OLS). The results show that IMDI and HDI have a positive and significant effect on formal financial activity, while RLS and GRDP are insignificant. Furthermore, there is a gap in AI readiness between regions, divided into high, medium, and limited categories. Regions with high readiness are dominated by Java Island and parts of Sumatra and Sulawesi, while Eastern Indonesia still faces limitations in digitalization, human resource quality, and formal financial activity. These findings indicate that financing decision-making in banking in the implementation of AI is more determined by digital transformation and HDI than RLS and GRDP.